(untitled) (UNWE Yearbook, 2009)
The main trends of public sector development are discussed in the study. The nature of the public sector is characterized; preconditions for its formation and functions performed are outlined.The research is directed to defining the priorities in the development of public sector after Bulgaria joined the EU. The focus of research is specific issues related to education, healthcare and public-private partnership.The main problems and tendencies in functioning of public organizations in the outlined priority areas are revealed. Opportunities for reforms speeding and improving the interactions among the public institutions in the country are suggested. On this base it is explained the necessity of using new approaches and concrete decisions for improving the activity of public organizations in Bulgaria under the conditions of integration to EU.